The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.46939/j.sci.arts-21.2-b04
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant, Cytotoxic and Antitumoral Activities of a Polyphenolic Extract of Robinia Pseudoacacia L. Flowers

Abstract: A polyphenolic extract of Robinia pseudoacacia L. flowers was prepared using a hydro-ethanolic extraction phase. The chemical analysis of the extract consisted in the assessment of the total polyphenolic content (Folin-Ciocalteu method) and the flavonoid fingerprint of the extract determined by high-performance thin-layer chromatography (HPTLC). Two methods ferric reducing antioxidant power (FRAP) and radical scavenging activity with DPPH were used to measure the antioxidant activity of the extract. The cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…They concluded that the 70% ( v / v ) methanolic and 80% ( v / v ) ethanolic extracts did not show cytotoxic activity against Vero African green monkey kidney cells because the IC 50 values (in that paper, IC 50 is presented as the LC 50 value) were higher than 1 mg/mL. Bratu et al [ 33 ] also confirmed the cytotoxic activity of 50% ( v / v ) ethanolic extract of black locust flower prepared via maceration against HeLa cells. That extract did not express the cytotoxic effect against the palatal mesenchymal stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the 70% ( v / v ) methanolic and 80% ( v / v ) ethanolic extracts did not show cytotoxic activity against Vero African green monkey kidney cells because the IC 50 values (in that paper, IC 50 is presented as the LC 50 value) were higher than 1 mg/mL. Bratu et al [ 33 ] also confirmed the cytotoxic activity of 50% ( v / v ) ethanolic extract of black locust flower prepared via maceration against HeLa cells. That extract did not express the cytotoxic effect against the palatal mesenchymal stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…Linalool, cis-β-ocimene, methyl anthranilate, phenyl ethyl alcohol, germacrene D, (E)-α-bergamotene, benzeneacetic acid methyl ester, (Z)-nerolidol, and indole are important contributors to the pleasant aroma of the flowers of R. pseudacacia [ 125 ]. The black locust flower polyphenolic extract contains a significant percentage of polyphenolic compounds and presents good antioxidant and antitumoral activity [ 126 ]. R. pseudacacia flowers are used in Italy as an infusion for the treatment of flu or as sedative [ 24 , 39 ], while in Turkey the infusion is used as a generic product which is good for health [ 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…During experiments, we were able to prove the increased antioxidant activity, as well as the in vitro antitumor effect of polyphenolic extracts of Robinia pseudoacacia flowers [12].…”
Section: Introductionmentioning
confidence: 95%
“…The mobile phase consisted of ethyl acetate-acetic acidformic acid-water 100:11:11:27 (v/v/v/v); as stationary phase pre-coated silica gel 60 F254 HPTLC plates were used (20 cm x 10 cm, Merck, Darmstadt, Germany). The sample application technique and the development mode were carried out according to the method described by Bratu et al, [12]. After development, the plates were dried at 105ºC for 10 min and derivatised in NP-PEG reagents [19].…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation